MOESM3 of Differential expression of the aryl hydrocarbon receptor pathway associates with craniofacial polymorphism in sympatric Arctic charr - Ahi, Ehsan; Steinhäuser, Sophie; Pálsson, Arnar; Sigrídur Franzdóttir; Sigurdur Snorrason; Maier, Valerie; Jónsson, Zophonías (Figshare, 2015)
Additional file 3: Table S3. Chd4-Cspp1-Dlg1 co-expressed genes in humans and mice retrieved from COXPRESdb. More than 200 genes were identified to have co-expression with Chd4, Cspp1 and Dlg1 after setting the mutual rank (MR) to the top-ranked 2000 genes and the reliability score of 1 to 3.